Aplikasi Sistem Penilaian Basic dan Intermediate Training Himpunan Mahasiswa Islam (HMI) Online - Kumarudin, Muhamad; , Umi Fadlilah, S.T., M.Eng (2016)
Islamic Student Association (HMI) is an Islamic student organization founded in Yogyakarta 14 Rabiul Awal 1366 H coincides with the date of February 5, 1947. There should not forget the student organization perkaderan process which will be the successor to the backbone of an organization. HMI cadre training is a conscious, planned, systematic, and continuous and has standard guidelines and regulations rationally in order to reach the destination HMI. The scoring system used in the assessment of the level of training the first level (LK 1) and the second level (LK 2) in the HMI is still manual, the process requires energy and the relatively long time. Therefore, the author makes an assessment system basic and intermediate training in HMI. HMI specially in Branch Sukoharjo-based web to assist instructors in the assessment process to be more effective and efficient. The method used in this study through the process of developing and designing a system with several stages of the planning system to system operation and maintenance phase. Systems designed with the programming language PHP using Dreamweaver applications, data is stored in a MySQL database. Application of this web-based assessment system consists of two sides of the admin and user. For admin or instructor is to help the assessment process data information along with the participants, and to this user HMI help aspiring cadres in the process of online registration.